Formation of accounts receivable of dairy products wholesale companies - Бєлозерцев, Василь Сергійович (Technology audit and production reserves, 2013)
The article studies the problems and peculiarities of formation of accounts receivable of dairy products wholesale companies. It determines the main features and peculiarities of the formation of the accounts receivables of dairy products wholesale companies. The article identifies the key moments that affect the formation of the accounts receivables and the debt relationships of the specified companies. There is an extension of manufacturers and distributors of dairy products and market consolidation. The concentration of major Ukrainian groups associated with the processing of milk and dairy products and the sale of dairy products has rapid pace. Foreign corporations in the domestic market affect the formation and management of accounts receivable. The companies are characterized by an increase of accounts receivables for goods as a result of fierce competition and a strategy of control of accounts receivable. There is a transformation of retail formats. Depending on the format of an outlet certain debt relationship between a wholesale company and a retail organization are created. It causes distortions of the development of certain industries. One of the features is the lack of regulations in economic and tax legislation to eliminate certain problematic moments in activity of retailers.